Analisa Faktor Eksternal yang Mempengaruhi Tingkat Return on Equity - Ady Inrawan; Hery Pandapotan Silitonga; Acai Sudirman (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2020)
The purpose of this study was to determine the effect of company external factors (inflation, interest rates, and exchange rates) on the ROE level. Associative research is used in this study with a qualitative approach. The object of research in companies of the Basic Industrial and Chemical Sub Sectors listed on the Indonesia Stock Exchange Period 2009 - 2018. Data collection techniques using the documentation method, data analysis techniques assumption of classiation, multiple linear regression, coefficient of determination and hypothesis testing. The results obtained, 1) Inflation, interest rates, exchange rates negatively affect ROE, 2) inflation rates, interest rates, and exchange rates affect ROE of 91.8%, 3) F test results, Inflation Rates, Interest Rates, and Exchange Rates have a significant effect on ROE.